Management Orientation of Members of Fish Farmers Producer Organizations (FFPOs) - Abdul Hannan Mondal,; Shyam Sundar Dana,; Moumita Ray , (Indian Journal of Extension Education, 2024)
A study was conducted in the Purba Medinipur district of West Bengal to assess the level of management orientation among 120 randomly selected fish farmer members from four purposefully selected FFPOs in 2023. Management orientation comprises the integration of planning, production, and marketing orientations.The study found that a significant portion of FFPO members fell into the medium planning orientation category (48.33%). A substantial proportion (43.33%) of respondents demonstrated a high level of production orientation. Most FFPO members (49.17%) demonstrated a medium level of marketing orientation. The distribution of planning, production, and marketing orientation levels among FFPO members indicates the need for capacity-building, targeted interventions to improve production capabilities, and optimization of marketing strategies. The 45.83 percent of respondents possessed a medium level of management orientation, whereas 35 percent exhibited a high level of management orientation. However, the overall management orientation remains inconsistent, with a need for enhanced training and capacity-building programs. Emphasizing continuous education on modern farming techniques and business management could bridge these gaps, leading to more efficient operations and higher economic gains for FFPO members.